2010
DOI: 10.1002/jmr.1085
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling‐based evaluation of dual function of IκBζ ankyrin repeat domain in toll‐like receptor signaling

Abstract: IkBz (inhibitor of NF-kB (nuclear factor kB) z) is a nuclear protein induced upon stimulation of toll-like receptors (TLRs) and interleukin-1 receptor. Induced IkBz, especially its C-terminal ankyrin repeat domain (ARD), interacts with NF-kB in the nucleus, where it regulates the transcriptional activity of target genes. Recent studies have shown that human ARD of IkBz binds with p50/p65 heterodimer and inhibits the transcription of NF-kB regulated genes, whereas mouse ARD of IkBz binds with p50/p50 homodimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
(69 reference statements)
8
16
1
Order By: Relevance
“…In IκBζ modelling, we deleted a 28 residue insertion, which was located between α1 and α2 of the fourth ANK repeat. The reason for deletion of this insertion region has been previously described [21]. Nevertheless, we also observed a 20 amino acid residues insertion in IκBNS corresponding to IκBζ.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…In IκBζ modelling, we deleted a 28 residue insertion, which was located between α1 and α2 of the fourth ANK repeat. The reason for deletion of this insertion region has been previously described [21]. Nevertheless, we also observed a 20 amino acid residues insertion in IκBNS corresponding to IκBζ.…”
Section: Resultssupporting
confidence: 82%
“…Since only the C-terminal dimerization region remained, we have hypothesized that this region might play a crucial role in the binding of IκB proteins. Our hypothesis is bolstered by previous data on the prediction of the Bcl3-p50/p50 and IκBζ-p50/p50 complexes [4], [21]. Additionally, cytoplasmic IκBε proteins mask the NLS of the p50/p65 complex, thereby preventing its translocation into the nucleus, and this is in agreement with previously solved cytoplasmic IκB proteins [13], [14], [16].…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…Although the structures are similar, the binding specificities of these proteins remain unknown. The modeling studies have identified that variation in charged surfaces among the IκB proteins and also differences in the flexible residual position might be the chief factor for the IκB protein binding specificities (Manavalan et al, 2010, 2011). …”
Section: Tir Mediated Downstream Activation and Inhibitionmentioning
confidence: 99%